Discriminação de argissolos e avaliação da estabilidade de agregados por vias seca e úmida em diferentes sistemas de uso e manejo - Perusi, Maria Cristina [UNESP] (2005)
In order to discriminate ARGISSOLOS and to evaluate aggregates stability by dry and humid ways under different use and management systems, it was studied soil profiles under agricultural and pasture for more than twelve five years on the following system: six years with annual crop rotation in areas that had been pasture for the same time period and forest, for comparison purposes. This study was done in a agricultural farm in the Anhumas county, São Paulo state, Brazil, where the predominant soil class - ARGISSOLO - are representative of the region. Stages to achieve the objectives: a) not deformed and deformed samples collection to perform chemical and physical analysis; b) determination of the aggregate percentage by dry and humid ways; c) computation of the weighted mean diameter of the aggregates (WMDA); d) soils classification; e) statistical analysis: variance analysis and Tuckey's test for average, at 5 % of probability. Main conclusions: soil classification; the organic matter content of the A horizon of the soil under forest is 64 % more than the soil under pasture e 79 % more than the soil under annual crop; the flocculation degree and amount of the clay fraction of this same horizon is 31 % more than the soil under pasture e 39 % more than the soil under annual crop; the weighted mean diameter of the aggregates obtained by dry (D) and (H) humid ways of the A horizon and its mean value for the soils decrease in the following sequence: PVAd - forest > PVe - pasture > PVd - annual culture, respectively, with the following values: 1.33560 and 1.445496 (D), 2.81114 and 2.351380 (H); 0.66748 and 1.011830 (D), 2.79642 and 1.624250 (H); 0.32468 and 0.993775 (D), 1.25808 and 0.983135 mm (H); the weighted mean diameters of the aggregates of the A horizon - obtained by dry (D) and humid (H) ways - decreased 50 % and 1 % in the soil under pasture... (Complete abstract click electronic access below)